#### Answer

r=-2

#### Work Step by Step

Simplifying
6r + -1(2r + -3) + 5 = 0
Reorder the terms:
6r + -1(-3 + 2r) + 5 = 0
6r + (-3 * -1 + 2r * -1) + 5 = 0
6r + (3 + -2r) + 5 = 0
Reorder the terms:
3 + 5 + 6r + -2r = 0
Combine like terms: 3 + 5 = 8
8 + 6r + -2r = 0
Combine like terms: 6r + -2r = 4r
8 + 4r = 0
Solving
8 + 4r = 0
Solving for variable 'r'.
Move all terms containing r to the left, all other terms to the right.
Add '-8' to each side of the equation.
8 + -8 + 4r = 0 + -8
Combine like terms: 8 + -8 = 0
0 + 4r = 0 + -8
4r = 0 + -8
Combine like terms: 0 + -8 = -8
4r = -8
Divide each side by '4'.
r = -2
Simplifying
r = -2